High School Aetas’ Course Experience: Benchmark for Streamlining Curricular Program Management - Payad, Arlan (JPAIR Multidisciplinary Research, 2024)
Many of the Aeta students in the province are included in mainstream classrooms.  As this causes the Indigenous some difficulty coping, the study analyzed four high schools regarding the course experience of 162 of their Aeta students.  The researcher used a survey that he, through referenced studies, localized and translated—”Survey on Aetas’ High School Course Experience.”  The survey yielded the most pronounced needs of Aetas—starting lessons with Aetas’ prior knowledge, school-based Indigenous centers, indigenized learning content, and more understandable media of instruction. The study used quantitative and descriptive, using a questionnaire to quantify the Aetas’ assessment of their high school experience with non-Indigenous classmates, teachers, and administrators. The study’s resulting discussion and conclusion suggested improvements through particularized versions of programs that could center on Inclusiveness Training for the teachers; school-based Indigenous Centers;  the inclusion of indigenous knowledge in lessons; implementation and consistent management of school services and events that reflect inclusive on-campus services; generation of livelihood programs and on-the-job trainings that are mindful of the job-readiness of the Aetas;  content training that is coupled with motivational counseling; the integration of technology that democratizes the access to information for all, with no exclusion against the non-mainstream.
Keywords: Indigenous; Aetas; high school; course experience; survey; program management; Pampanga; policy development; Philippines